A study of advertising elements on the depression disorder that leads to suicide / Nazreev Ridzuan - Ridzuan, Nazreev (2019)
Suicide is one of the most serious mental-health issues but apparently, it is very challenging to determine the most optimal method to prevent one from committing suicide. Suicide prevention through media reporting on suicidal behaviours is recognised to be one of the public health approaches in dealing with this issue. Hence, the aim of this study is to investigate the possible benefits and effects of suicide prevention resulting from the advertising impact specifically referring to the Public Service Announcements (PSAs) for the youth. The type of method that will be conducted for this research is by investigating two types of respondents which are categorized into one depression state and a non-depression state. The effects will be laid down by the researcher to study the types of advertising or PSA will be more effective to these parties. This research is urgently performed so that well-intended efforts to prevent suicide can be fully optimized to achieve the desired goal.